(Civilni) sodnik in ustava - Wedam-Lukić, Dragica (Pravni letopis, 2010)
The article deals with the duties of judges in ordinary courts of law concerning the application of the Constitution when deciding in particular cases. Pursuant to Article 125 of the Constitution, judges are bound not only by laws but also by the Constitution. Consequently, judgesmust be familiar with the case-law of the Constitutional Court and must apply its decisions in interpreting laws. If the court deems a law or a part thereof which it should apply to be unconstitutional, it must stay the proceedings and initiate proceedings before the Constitutional Court. The author believes that this duty of ordinary courts hasbecome even more important because of the recent case-law of the Constitutional Court according to which a petitioner has no legal interest to initiate the procedure for the review of the constitutionality or legality before he has exhausted all means of appeal before ordinary courts also in this regard.
Keywords: civilno pravo; pravosodje; pristojnosti; sodišča; ustave